Women and Islamic Financial Literacy - Amaroh, Siti; Istianah, Istianah (PALASTREN: Jurnal Studi Gender, 2020)
This study aims to understand about Islamic financial literacy of women’s groups. The measurement includes financial goals and concepts, efforts to achieve financial goals, preferences for financial institutions both in product and services, knowledge of Islamic financial literacy, and financial practices. This study used survey method and carried out in 64 female respondents with various professional backgrounds. This research found several findings. The main financial purposes are to fulfill basic need, children’s education costs, and survive. The efforts to achieve financial goals are by working, saving, or reducing expenditure. When respondents have a surplus of money, they choose for saving, pay for the hajj or umrah, or support orphans and the poor. Saving and pension funds will be used to meet requirement in the elderly. Financial security if lack of money or loss of income was by take saving, find a new job, or open a business. Bank is the main choice in carrying out of financial transaction, the pension fund and health insurance. The preferred informal financial institution is social gathering or called as “arisan”. Respondents prefer to choose Islamic financial institutions due to fit with religious values and give an inner peace, however not refuse to choose conventional financial institutions because it is guaranteed by the governance. The knowledge of Islamic finance is quite good (sufficient literate) with a correct answer score at 51% to 75%. While the financial practices that have been carried out are saving, transferring, and paying installments.